PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN SALES GROWTH TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Dyah Anggraini; Raja Adri Satriawan Surya; Adhitya Agri Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to examine the effect of corporate governance, profitability,leverage, company size, and sales growth on tax avoidance in manufacturing companieslisted on the Indonesia Stock Exchange in 2015-2017 and this study aims to examine theeffect of independent variables that can significantly affect or not to tax avoidance. Thepopulation used in this study was based on predetermined criteria and a total of 51companies for 3 years, then the total sample was 153 samples. This study used apurposive sampling method and tested the hypothesis using multiple linear regressionanalysis using SPSS 22 version software. The results of this study show that theindependent variables of profitability have an effect on tax avoidance, and corporategovernance, leverage, firm size and sales growth do not affect tax avoidance. The resultsof the coefficient of determination (adjusted R2) of 0.166. This means that the overalleffect of the independent variable on tax avoidance is 16.6% while the remaining 83.4%is influenced by other independent variables not used in this study.Keywords : corporate governance, profitability, leverage, company size, sales growth,tax avoidance.